NETs promote invasive behavior of fibroblast-like synoviocytes through GPIbα in rheumatoid arthritis - Zhang, Yongqiang; Wu, Yingyi; Yang, Hui; Liu, Xuanqi; Pan, Bing; Ding, Congzhu; Sun, Yue; Sun, Lingyun (Frontiers in Immunology, 2025)
ObjectiveNeutrophil extracellular traps (NETs) have been implicated in rheumatoid arthritis (RA) pathogenesis, yet their effects on fibroblast-like synoviocytes (FLS) remain unclear. This study aims to investigate the role of NETs in RA FLS migration, proliferation, and invasion, as well as the underlying molecular mechanisms.MethodsNETs formation was assessed in neutrophils isolated from RA patients and healthy controls (HC) using immunofluorescence staining. RA FLS were stimulated by RA or HC derived NETs, and migration was evaluated via wound healing assays. RNA sequencing (RNA-seq) identified differentially expressed genes in FLS, validated by qPCR. The expression and localization of glycoprotein Ib alpha (GPIbα) in RA synovium were examined by immunohistochemistry. GPIbα was knocked down in FLS to assess its role in proliferation and migration. A collagen-induced arthritis (CIA) model was used to study the effect of NETs inhibition on RA progression.ResultsRA neutrophils produced more NETs than HC neutrophils. RA NETs enhanced FLS migration and proliferation, and RNA-seq revealed upregulation of GP1BA, which was confirmed by qPCR. GPIbα expression was elevated in RA synovium. GP1BA knockdown suppressed RA NETs-induced FLS proliferation and migration. In CIA mice, inhibiting NETs formation decreased GPIbα expression, limited FLS invasiveness, and attenuated RA progression.ConclusionOur findings reveal that NETs promote RA progression by inducing FLS proliferation and migration through GPIbα. Consequently, targeting NETs formation or GPIbα represents a promising therapeutic strategy to mitigate RA.